2017
DOI: 10.1200/jco.2017.35.15_suppl.7519
|View full text |Cite
|
Sign up to set email alerts
|

Response rates with pembrolizumab in combination with rituximab in patients with relapsed follicular lymphoma: Interim results of an on open-label, phase II study.

Abstract: 7519 Background: Follicular lymphoma (FL) tumors are infiltrated with antitumor T cells, however, their function is impaired by immune checkpoints such as PD-1/PD-ligand pathway. Blocking PD-1 enhances the function of antitumor T cells in FL. In addition, blocking PD-1 on NK cells has been shown to enhance the ADCC effect of NK cells. We reasoned that the combination of pembrolizumab (P), an anti-PD-1 antibody (ab), and rituximab (R), an anti-CD20 ab that induces ADCC, is likely to be synergistic through acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…111 The combination of pembrolizumab and rituximab showed a high ORR of 80% in relapsed FL. 112 High complete response rates (50% to 65%) have been reported for the combination of nivolumab and brentuximab vedotin in patients with R/R HL in 2 phase 1/2 trials. 113,114 Nivolumab and pembrolizumab showed acceptable safety profiles with low rates of discontinuation resulting from adverse events, although close monitoring is warranted, especially for patients with a history of acute graft-versus-host-disease.…”
Section: Pd-l1 Expression and Clinical Roles In B-cell Lymphomasmentioning
confidence: 97%
See 2 more Smart Citations
“…111 The combination of pembrolizumab and rituximab showed a high ORR of 80% in relapsed FL. 112 High complete response rates (50% to 65%) have been reported for the combination of nivolumab and brentuximab vedotin in patients with R/R HL in 2 phase 1/2 trials. 113,114 Nivolumab and pembrolizumab showed acceptable safety profiles with low rates of discontinuation resulting from adverse events, although close monitoring is warranted, especially for patients with a history of acute graft-versus-host-disease.…”
Section: Pd-l1 Expression and Clinical Roles In B-cell Lymphomasmentioning
confidence: 97%
“…Across lymphoma entities, anti-PD-1 monotherapy showed the greatest efficacy in R/R cHL. [20][21][22][23]76,[107][108][109][110][111][112][113][114][115] In a phase 1 trial of nivolumab, the objective response rate (ORR) was remarkable (87%). 20 In phase 2 trials, nivolumab and pembrolizumab had similar ORRs (68% and 69%) and OS rates (99%) at 6 months, 22,23 leading to accelerated FDA approval in 2016 for nivolumab and in 2017 for pembrolizumab.…”
Section: Pd-l1 Expression and Clinical Roles In B-cell Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results from these novel treatment approaches are encouraging, demonstrating improved response rates 102,103 . …”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…Regarding checkpoint blockade, it can be expected that a combinational approach of passive immunotherapy (anti-CD20) with anti-PD1 antibodies has potential. At the ASH meeting 2017, first data from a trial combining rituximab with pembrolizumab were shown ( 30 ). Here, 30 patients with relapsed FL received rituximab plus pembrolizumab for a total of 16 infusions.…”
Section: Checkpoint Blockade Inhibiting Antibodiesmentioning
confidence: 99%